The Other Lola : a novel - Jones, Ripley; Jones, Ripley (New York : Wednesday Books, 2024)
Despite their resolution to avoid mysteries and podcasts, Cam and Blair re-enter investigative mode when Mattie Brosillard seeks their help, convinced that someone is impersonating her sister Lola, who disappeared five years ago.
new ya book 2024 spring.
Ages 13-18.
Keywords: Mystery and detective stories; Podcasts -- Fiction; Missing persons -- Fiction; Impersonation -- Fiction; Detective and mystery fiction; Novels; Detective fiction; Mystery fiction